Unpacking Power Relations: Stakeholder Dynamics and the Future of Organic Farming in Bogor Regency, Indonesia - Handoyo; Subarudi; Syahyuti; Wibowo, Lukas Rumboko; Budiningsih, Kushartati; Harianja, Alfonsus H.; Rahmayanti, Atika Zahra; Iqbal, Mohamad; Septina, Ane Dwi; Hafsari, Tria Anggita; Sanusi (The International Journal of Sociology of Agriculture and Food, 2025)
This paper explores how organic farming unfolds in Bogor Regency, Indonesia, by looking closely at the power dynamics that shape its meaning, practices, and governance. Rather than treating organic farming as a fixed technical system, we approach it as a contested space where farmers, state agencies, NGOs, certification bodies, and private actors bring different values, interests, and forms of authority. Using a combination of stakeholder power analysis (SPA), political ecology, and food regime theory, the research draws on in-depth interviews and focus group discussions in two villages with contrasting institutional landscapes. We find that key barriers, such as high certification costs, limited market support, and fragmented policy implementation, are not simply technical problems but reflect deeper struggles over who gets to define sustainability. In response, smallholder farmers and civil society actors are creating grassroots innovations, including peer-to-peer mentoring systems and participatory guarantee schemes, that reclaim agency from top-down structures. Still, institutional silos and the lack of meaningful coordination continue to undermine inclusive progress. Our findings call for stronger connections across institutional boundaries. We argue that building trust-based spaces of dialogue between certification agencies, advisory services, and farmer networks is essential not only to make organic farming more viable, but also to ensure that it reflects the lived realities and aspirations of those who practice it. By foregrounding local knowledge and ethical commitments, this study contributes to broader conversations on agroecological transitions and more just food systems.